2017
DOI: 10.1002/jrs.5311
|View full text |Cite
|
Sign up to set email alerts
|

On‐site Raman study of artwork: Procedure and illustrative examples

Abstract: Raman microspectroscopy conducted with transportable/mobile instruments allows for the non‐invasive identification of amorphous and crystalline phases of ancient masterpieces and outstanding artworks (objects, paintings and décor, building parts, etc.). Resonance Raman spectroscopy detects chromophore and dye traces. On the basis of examples (enamelled glass and pottery, enamelled metal, patinated/corroded metal, stained glass, sculptures, paintings, pastels, and drawings), this mini review discusses the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 116 publications
(245 reference statements)
1
46
0
Order By: Relevance
“…The absolute Raman intensity of the silicate signature was found to be an effective tool in the discrimination of similar types of glasses as a function of time according to their varying degrees of corrosion, which in turn affect the transparency of glass . The relative intensity of the Raman signature of protonic species incorporated in the glassy silicate network on the glass or glaze surface was also previously proposed as a potential tool for the discrimination of artefacts (kept in the same conditions) as a function of age . The results of our analyses on different types of glazed pottery samples showed that there is a correlation between the relative intensity of the broad Raman signature of the protonic species and the age of the artefact to a certain degree including the celadon or stoneware and porcelain samples.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…The absolute Raman intensity of the silicate signature was found to be an effective tool in the discrimination of similar types of glasses as a function of time according to their varying degrees of corrosion, which in turn affect the transparency of glass . The relative intensity of the Raman signature of protonic species incorporated in the glassy silicate network on the glass or glaze surface was also previously proposed as a potential tool for the discrimination of artefacts (kept in the same conditions) as a function of age . The results of our analyses on different types of glazed pottery samples showed that there is a correlation between the relative intensity of the broad Raman signature of the protonic species and the age of the artefact to a certain degree including the celadon or stoneware and porcelain samples.…”
Section: Discussionsupporting
confidence: 54%
“…A broad component is observed with submaxima at 2,700, 2,900, and 3,180 cm −1 . The broad bands at 2,700 and 2,900 cm −1 indicate the strongly H‐bonded species whereas the band at 3,180 cm −1 is assigned to the water molecules adsorbed at the glass surface or within the cracks . A weak broad band visible at 3,300 cm −1 also indicates the presence of water molecules in the sample whereas another weak narrow band at 3,730 cm −1 is assigned to the hydroxyl groups (Table and Figure b).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations